The effects of alcohol on the fetus, and pregnancy outcome. Fetal alcohol syndrome and fetal alcohol spectrum disorders - N. V. Protopopova; L. Kolesnikova; A. Y. Marianian (Acta Biomedica Scientifica, 2013)
In a review of the scientific literature describes the current understanding of the problem of the teratogenic effects of alcohol on the fetus, and pregnancy outcome. Attention is paid to the occurrence, clinical manifestations of fetal alcohol syndrome and fetal alcohol spectrum disorders. It is shown that in Russia accurate epidemiological data on the incidence of fetal alcohol syndrome and fetal alcohol spectrum disorders are not available. It is noted that the use of alcohol by women is associated with adverse pregnancy outcome. May manifest clinically delayed fetal development, risk of miscarriage and low birth weight. In reviewing the domestic and foreign literature revealed that in Russia the problem is insufficiently known, relevant. Therefore, the study of this problem will be of great theoretical and practical significance.